Disclosures on control over financial reporting: The reporting practice of banks listed on the Warsaw Stock Exchange - Jacek Gad (e-Finanse: Financial Internet Quarterly, 2015)
The purpose of this paper is to identify the effects of the implementation of selected regulations on corporate governance in the reporting practice of banks listed on the Warsaw Stock Exchange. The survey examined the disclosures concerning the main features of the internal control and risk management systems in relation to financial reporting in banks. Research studies on disclosures related to control over financial reporting have not yet been conducted. The paper uses a research method involving the analysis of annual reports disclosed by banks. The method of induction was used in the process of inference. The results of the study indicate that in the practice of reporting of banks listed on the Warsaw Stock Exchange in 2011, there was no uniform reporting form in terms of the presentation of information on internal control or risk management systems in relation to financial reporting. The disclosures were different both in terms of level of detail and content. In some banks disclosures were drawn at a high level of generality.
Keywords: M48; M41; G34; 330; banks; financial reporting; disclosures; control over financial reporting